Assessment of The Socio-Economic Performance of G-20 Countries Via The Critic-Aras Method (Third Sector Social Economic Review, 2025)
This study aims to evaluate and compare the socio-economic performances of G-20 countries from 2018 to 2021 utilizing the ARAS method, a Multi-Criteria Decision-Making technique. The objective is to scrutinize and juxtapose these performances by employing assessment criteria such as the Life Ladder, GDP per capita, Freedom to Make Life Choices Indicator, Corruption Perceptions Index, Human Development Index, Sustainable Development Index, Global Terrorism Index, and Global Peace Index. To determine the importance levels of evaluation criteria, the CRITIC method, one of the objective techniques, has been utilized. Moreover, with the importance levels calculated through this method, the inclusion or exclusion of the preferred evaluation criteria in the model has also been assessed. Analysis of the study indicates that the Global Terrorism Index was identified as the most important criterion, while the Life Ladder indicator was deemed the least important. Within the G-20 countries, Japan secured second place in 2019, subsequently dominating the top rank in all subsequent years. Australia, leading the rankings in 2019, transitioned to second place the following year, persisting in third place for 2020 and 2021. Notably, Turkey consistently maintained the 18th rank among G-20 countries, with an exception in 2019 when it held the 17th place.  In contrast, India held the 18th place in 2019 but maintained the 17th rank in all other observed years.
Keywords: CRITIC Method; ARAS Method; Multi-Criteria Decision Making; Socio-economic Indicators; G-20 Countries